Novel Millimeter-Wave Bandwidth-Controllable Filtering Antenna Based on Composite ESPPs-SIW Structure - Zhang, Xue-Feng; Cao, Shuai-Hua; Chen, Jian-Xin (IEEE transactions on antennas and propagation, 2021)
A bandwidth-controllable filtering antenna based on composite effective surface plasmon polaritons (ESPPs)-substrate integrated waveguide (SIW) structure is presented. The composite ESPP-SIW structure can support ESPPs at some frequencies. The asymptotic characteristic of ESPPs is employed to form a bandpass filter, which consists of an SIW and an air cavity situated on the top of the SIW. The unequal widths and the different dielectrics of the cavity and the SIW are employed to provide flexible controllability on the dispersion of ESPPs and thus on the cutoff frequencies of the ESPPs-SIW structure. By engineering the structural dispersion of ESPPs, the filter based on ESPPs-SIW structure shows independent controllability on its cutoff frequencies and thus exhibits a controllable bandwidth. Moreover, from effective-medium aspect, an analytical method is provided to guide the filter design. The filter is used to construct a filtering antenna operating at 5G millimeter-wave (MMW). A prototype of the filtering antenna is fabricated by using multilayer printed circuit boards (PCBs). Simulated and measured results show a good skirt selectivity and flat antenna gain in the passband (22-28 GHz) and also a high suppression in the stable wide stopband (30-43 GHz).